Smart Earth: A meta-review and implications for environmental governance. (September 2018) - Bakker, Karen; Ritts, Max
Highlights: Smart Earth is an innovative approach to environmental monitoring. Smart Earth combines conventional monitoring with ICT and the Internet of Things. This paper presents a meta-review of 3187 articles over the period 1997 to 2017. Implications for environmental governance include real-time regulation; enhanced predictive management; and citizen sensing. Abstract: Environmental governance has the potential to be significantly transformed by Smart Earth technologies, which deploy enhanced environmental monitoring via combinations of information and communication technologies (ICT), conventional monitoring technologies (e.g. remote sensing), and Internet of Things (IoT) applications (e.g. Environmental Sensor Networks (ESNs)). This paper presents a systematic meta-review of Smart Earth scholarship, focusing our analysis on the potential implications and pitfalls of Smart Earth technologies for environmental governance. We present a meta-review of academic research on Smart Earth, covering 3187 across the full range of academic disciplines from 1997 to 2017, ranging from ecological informatics to the digital humanities. We then offer a critical perspective on potential pathways for evolution in environmental governance frameworks, exploring five key Smart Earth issues relevant to environmental governance: data; real-time regulation; predictive management; open source; and citizen sensing. We conclude by offering suggestions for future research directions and trans-disciplinary conversations about environmental governance in a Smart Earth world.